Demographic, radiological and pathological profile of head and neck cancers - S., Prahlad M.; Appaji, Mohan K.; Y., Kavitha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Objective of the current study was to assess incidence of various head and neck cancers, their demographic, radiological, pathological characteristics and patterns of regional lymph node metastasis. Methods: This is a retrospective analysis of data available from medical records department in our institution from the period of January 2017 to November 2020. Patients as per inclusion and exclusion criteria, were selected, the disease was staged and analyzed. Results: Males were more commonly affected (78%). Among the upper aerodigestive tract cancers, lip and oral cavity cancers were most common (26%). Most common stage at presentation was stage IV A. Cervical lymph node metastasis was present in 69% of cases. Most common upper aerodigestive tract cancer was squamous cell carcinoma. Most common thyroid malignancy was papillary carcinoma. Conclusions: Head and neck cancers have high morbidity and mortality owing to advanced stage of presentation and cervical lymph node metastasis affects the outcome of the disease adversely. Every case of head and neck malignancy, hence, need to be evaluated thoroughly and staged appropriately before taking treatment decisions.